Statistical Parametric Mapping Differences in Muscle Recruitment Patterns Between Comfort- and Performance-Oriented Saddle Positions - Sławomir Winiarski; Adam Kubiak; Adam Paluszak (Applied Sciences)
This study investigates whether electromyography (EMG) analysis can reflect ergonomic improvements for commuter bike users by assessing muscle activity differences between comfort- and performance-oriented saddle positions. A cohort of 30 city bike riders underwent a comprehensive fitting procedure, where one position was individually established based on a comfort perception questionnaire and adjusted by a bike fitter. The aim was to compare the EMG activity of muscles involved in propulsion and lumbar spine stabilisation across different positions. The Statistical Parametric Mapping (SPM) method was also used to analyse muscle activity throughout the pedalling cycle. The results revealed that the customised position significantly reduced EMG activity in muscles, particularly during key pedalling phases, significantly improving rider comfort and muscle efficiency. SPM analysis highlighted decreased strain in the vastus lateralis and tibialis anterior, indicating improved muscular efficiency and enhanced comfort for urban cyclists. This underscores the importance of personalised bike fitting in promoting comfort and reducing the risk of injury, suggesting that EMG analysis is a valuable tool in both clinical and recreational bike-fitting practices. Future research should explore the long-term effects and potential applications of the proposed fitting method for other bicycle geometries whenever comfort and lower back stability are priorities.